The big pets - Smith, Lane. (New York, N.Y., U.S.A. : Puffin, 1993)
A little girl explores the mysterious dreamworld where small children play with their big pets, which range from cats and dogs to snakes and crickets.
"First published in the United States of America by Viking Penguin ... 1991"--T.p. verso.
Booklist.
Publisher's Weekly.
4.1
K-3.
K-3
Keywords: Animals -- Fiction; Dreams -- Fiction; Pets -- Fiction; Animals -- Fiction; Dreams -- Fiction; Pets -- Fiction